POTENSI KONFLIK DI WILAYAH PERBATASAN DARAT REPUBLIK INDONESIA-REPUBLIK DEMOKRATIK TIMOR LESTE (STUDI KASUS DI KABUPATEN TIMOR TENGAH UTARA PROVINSI NUSA TENGGARA TIMUR) - Nur Julqurniati; Dewi Indah Susanty (UNIVERSITAS SEBELAS MARET (UNS), 2019)
Various conflict potentials that can be found in North Middle Timor (TTU) Regency can interfere orderliness and security as well as hinder the development in border regions. This research aims to describe any sources and factors triggering conflict potentials, as well as any efforts to eradicate the social conflict potentials in west border regions of the Republic of Indonesia (RI) - Democratic Republic of Timor Leste (RDTL). Research method was by qualitative with a study case approach. The informants were determined by purposive and snowball sampling techniques, meanwhile data collection techniques were conducted by observation, interview and documentation. Results of the study indicate that identified conflict potentials in TTU Regency are activities of illegal trading, boundary and ulayat land as well as thievery and cattle crossing. Conflict potentials that can be found from illegal trading activity are caused by economic factor and needs that are blocked by domination of apparatus in border regions. In the issues of boundary and ulayat land, the conflict potentials are caused by differences in determining the boundary between the central government and TTU border citizens. In the issues of thievery and cattle crossing, the conflict potentials are caused by accumulation of citizen hatred, social prejudice and lack of government role in maintaining security in border regions. The efforts of conflict potential management related to illegal trading activity are by giving recommendation and socialization in order to conduct the trading activity through legal channel and making informal agreement between citizen and apparatus in border regions. The effort to solve conflict potentials related to boundary and ulayat land issues is conducting negotiation between central government of RI and traditional leaders, and negotiation between traditional leaders of RI and RDTL. The effort to solve thievery and cattle crossing issues is also by conducting a customary agreement. Keywords: Land Border, Illegal Trading, Conflict Potentials, Boundary AbstrakBerbagai potensi konflik yang ada di Kabupaten Timor Tengah Utara (TTU) dapat mengganggu ketertiban dan keamanan, serta menghambat pembangunan di wilayah perbatasan. Penelitian ini bertujuan untuk mendeskripsikan sumber dan faktor-faktor penyebab munculnya potensi konflik, serta upaya-upaya untuk mencegah potensi konflik sosial di wilayah perbatasan darat Republik Indonesia (RI) – Republik Demokratik Timor Leste (RDTL). Metode penelitian yang digunakan adalah kualitatif dengan pendekatan studi kasus. Informan ditentukan dengan teknik purposive dan snowball sampling, sedangkan teknik pengumpulan data dilakukan dengan observasi, wawancara dan dokumentasi. Hasil kajian menunjukkan potensi konflik yang terindentifikasi di Kabupaten TTU adalah aktivitas perdagangan ilegal, tapal batas dan tanah ulayat, serta pencurian dan perlintasan ternak. Potensi konflik yang dapat timbul dari aktivitas perdagangan ilegal disebabkan oleh faktor ekonomi dan kebutuhan yang dihalangi dengan adanya dominasi aparat di wilayah perbatasan. Pada permasalahan tapal batas dan tanah ulayat potensi konflik disebabkan oleh perbedaan dalam menentukan batas negara antara pemerintah RI dengan penduduk perbatasan TTU. Pada permasalahan pencurian dan perlintasan ternak, faktor penyebab munculnya potensi konflik adalah akumulasi kebencian penduduk, adanya prasangka sosial dan kurangnya peran pemerintah dalam menjaga keamanan di perbatasan. Upaya pengelolaan potensi konflik terkait aktivitas perdagangan ilegal adalah memberikan himbauan dan sosialisasi agar melakukan aktivitas perdagangan lewat jalur resmi, dan kesepakatan informal antara penduduk dengan aparat perbatasan. Upaya yang dilakukan untuk potensi konflik terkait permasalahan tapal batas dan tanah ulayat adalah negosiasi antara pemerintah pusat dan tokoh adat serta negosiasi antara tokoh adat kedua negara. Upaya yang dilakukan terkait pencurian dan perlintasan ternak adalah membuat kesepakatan adat. Kata kunci: Perbatasan Darat, Perdagangan Ilegal, Potensi Konflik, Tapal Batas